The perceptions of black psychotherapy supervisee's in supervision with white supervisors - Naidu, Kevin (My University, 2009)
In the past, Black people had little access to psychological services in their communities. Historically, Black people were not allowed free access to psychological training in South Africa. After the new dispensation of 1994, however, the establishment of affirmative action policies changed the face of professional psychology training programs in South Africa. The number of Black people accepted into training programs has increased as a result of these policies. The need to understand how Black supervisees experience psychotherapy supervision with a White supervisor is therefore of critical importance, given the prevalence of White supervisors’. It is apparent that there have been few studies done in South Africa dealing directly with the issue of racial dynamics within psychotherapy supervision. This study was aimed at exploring how Black psychodynamic psychotherapy supervisees experience psychotherapy supervision with White supervisors, and how this racial difference is perceived to influence the supervisory relationship. In order to explore these aims, a qualitative approach, thematic content analysis was adopted to encourage the participants to voice their opinions. The results of this study indicate that Black supervisees often experience themselves as passive and inferior in relation to their White supervisors. This study also indicates that the issue of racial difference needs to be discussed openly by White supervisors and Black supervisees. In addition, the study suggests that Black supervisees may need their White supervisors to take an active interest in attempting to understand the values and beliefs associated with their racial background.
Keywords: psychotherapy